Effectiveness Of Liquid Smoke from Oil Palm Solid Waste Against Spodoptera frugiperda (lepidoptera: noctuidae) - Ainun, Khairunissa; Giffari, Fahri Rijal; Widayani, Neneng Sri; Fathussalam, Muhammad; Haryadi, Dudi; Yuwono, Indra; Dono, Danar (CROPSAVER, 2023)
Indonesia is one of the largest producers of palm oil commodities in the world. Massive palm oil production to meet high demand can pose risks in increasing waste production. The processing of solid palm oil waste into liquid smoke through pyrolysis is carried out as an effort to mitigate environmental damage caused by greenhouse gases. Components in liquid smoke can be utilized as natural insecticides. This research aims to determine the potential of liquid smoke from solid palm oil waste, namely fiber and frond, to control Spodoptera frugiperda. The testing method uses a Randomized Complete Block Design (RCBD) with 11 treatments repeated three times. Liquid smoke application is done by dipping the feed, which is then given to S. frugiperda instar II. The results show that liquid smoke from fronds causes higher mortality in S. frugiperda compared to liquid smoke from fibers. At a concentration of 4%, liquid smoke from fronds and fibers caused S. frugiperda mortality of 63.33% and 40%, respectively. Liquid smoke application also suppressed feed consumption by 72.98% lower than the control and caused an extension of time from instar II-VI at the 4% application concentration. The use of liquid smoke from palm fronds and fibers can be used as an insecticide as one of the pest control techniques and a solution for utilizing palm oil waste.